Clinical indications, complications, and outcomes of internal bleaching - Alanazi, Anwar R.; Albalawi, Ohood A.; Alasmari, Saeed O.; Almulhim, Sakhr A.; Altowejri, Safaa S.; Marzok, Naser M.; Alqarani, Majed A.; Alsaiad, Sohair A.; Al Shehri, Wael A.; Alanazi, Fares R. (International Journal Of Community Medicine And Public Health, 2022)
Different bleaching treatments may be used to try to remove intrinsic stains and more tenacious extrinsic discoloration. Intracoronal tooth whitening, sometimes known as non-vital tooth whitening can be used to whiten teeth. By oxidizing the organic discoloration in the tooth, the bleaching treatment lightens the color of the teeth. The underlying etiology of the discoloration affects the effectiveness and efficacy of tooth bleaching. Internal bleaching is a minimally invasive and cost-effective dental technique that doesn't alter the tooth's size or position on the dental arch. Trauma can cause a tooth to become nonvital and lose its natural color without ever requiring endodontic treatment. In these situations, the first course of treatment should be a root canal. We can move forward with the internal bleaching technique if the tooth has had endodontic treatment. Before placing all ceramic restorations, an interior bleaching may occasionally be required too. Pulp chamber origin discoloration is an indication for internal bleaching. Inflammation-mediated external root resorption known as cervical root resorption can occur after trauma and after intracoronal bleaching. Another internal bleaching issue was the coronal fracture, which is thought to have been brought on by desiccation or changes to the physicochemical properties of the dentin and enamel. The absence or minimal color difference between the treated and untreated teeth has traditionally been considered a sign of immediate treatment efficacy.